2018
DOI: 10.1038/s41598-017-18067-6
|View full text |Cite
|
Sign up to set email alerts
|

Large area growth of MoTe2 films as high performance counter electrodes for dye-sensitized solar cells

Abstract: A cost effective and efficient alternative counter electrode (CE) to replace commercially existing platinum (Pt)-based CEs for dye-sensitized solar cells (DSSCs) is necessary to make DSSCs competitive. Herein, we report the large-area growth of molybdenum telluride (MoTe2) thin films by sputtering-chemical vapor deposition (CVD) on conductive glass substrates for Pt-free CEs of DSSCs. Cyclic voltammetry (CV), Tafel curve analysis, and electrochemical impedance spectroscopy (EIS) results showed that the as-synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 43 publications
(39 reference statements)
5
27
0
Order By: Relevance
“…Since the discovery of topological superconductivity and large magnetoresistance in this compound it has been the subject of comprehensive fundamental research [11][12][13][14] . In addition, 1T′-MoTe 2 has been highlighted as an emerging energy material with applications ranging from photovoltaic cells to hydrogen evolution catalysis [15][16][17] . Furthermore, few-layered 1T′-MoTe 2 may become a promising sensing platform enabled through its ability to suppress fluorescence signals which often prevents reliable detection of Raman scattering from negligible traces of molecules 18 .…”
mentioning
confidence: 99%
“…Since the discovery of topological superconductivity and large magnetoresistance in this compound it has been the subject of comprehensive fundamental research [11][12][13][14] . In addition, 1T′-MoTe 2 has been highlighted as an emerging energy material with applications ranging from photovoltaic cells to hydrogen evolution catalysis [15][16][17] . Furthermore, few-layered 1T′-MoTe 2 may become a promising sensing platform enabled through its ability to suppress fluorescence signals which often prevents reliable detection of Raman scattering from negligible traces of molecules 18 .…”
mentioning
confidence: 99%
“… 41 The PCEs of the α-AuSe CE is comparable to some of the reported PCEs of different layered materials as CEs. Examples include; 6.23% for graphene, 20 6.6% for MoS 2 , 21 7.01% for MoSe 2 , 22 6.30% for WS 2 , 42 7.25% for MoTe 2 , 43 7.99% for WS 2 /MoTe 2 , 44 7.66% for TiS 2 and 8.80% for TiS 2 nanosheets assembled and decorated on graphene (TiS 2 –G) 16 as shown in Fig. 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, the peaks at negative potential correspond to the reaction and other peak at positive potential corresponds to the reaction In DSSC, the reduction reaction of I 3 − will take place in the counter electrode to complete the circuit conductivity and to regenerate the dye molecules and hence it is necessary to study the oxidation and reduction of I − /I 3 − at negative potential side. It is reported that the electrocatalytic ability of a counter electrode for an I 3 − reduction in DSSC relates to the cathodic peak current at more negative potential 42 . The higher the cathodic peak current density, better the catalytic activity of the counter electrode 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%